Pengaruh Persepsi dan Ketekunan Belajar Matematika Terhadap Hasil Belajar pada Materi SPLDV - Abida Wadiatun Ilahi; Sripatmi, Sripatmi; Amrullah, Amrullah; Laila Hayati (Griya Journal of Mathematics Education and Application, 2025)
This research aims to determine the relationship between the perceptions of class VIII students at SMPN 13 Mataram regarding mathematics and their learning persistence, partially with learning outcomes, and the influence of both simultaneously on learning outcomes. The type of research used is ex-post facto research with a quantitative approach. The research instruments used were perception questionnaires, study persistence questionnaires, and tests on SPLDV material. The research sampling technique used simple random sampling, using 30 class VIII students at SMPN 13 Mataram as samples. Before taking samples, a homogeneity test was carried out on the population, it was found that the population was homogeneous. The results of this study show that there is a relationship between perceptions and learning outcomes, but with a relatively low correlation. Likewise, between persistence and learning outcomes, there is a relationship with a correlation that is classified as very low. The correlation test results are 0.253 and 0.162, respectively. However, simultaneously, perceptions and learning outcomes have a significant influence on learning outcomes. This is shown by Fcount (3.682) > Ftable (3.35). The regression equation obtained is Ŷ = 0.8 + 0.6X1 + 0.1X2.